2015
DOI: 10.1007/s11010-015-2525-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective efficacy of naringin on 3-nitropropionic acid-induced mitochondrial dysfunction through the modulation of Nrf2 signaling pathway in PC12 cells

Abstract: quinone oxidoreductase-1 and Heme oxygenase-1 expressions through the phosphatidylinositol-3-kinase (PI3K)/Akt signaling pathway. Taken together, the above findings suggest that naringin augments cellular antioxidant defense capacity and reduces the 3-NP-induced neurotoxicity in PC12 cells through the PI-3K/Akt-dependent Nrf2 activation in PC12 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…The presence of naringin may have triggered the activation Nrf2 signalling pathway reducing the DOX induced oxidative stress. 80 …”
Section: Discussionmentioning
confidence: 99%
“…The presence of naringin may have triggered the activation Nrf2 signalling pathway reducing the DOX induced oxidative stress. 80 …”
Section: Discussionmentioning
confidence: 99%
“…Naringin ameliorates cognitive deficits via oxidative stress, proinflammatory factors and the PPARγ signaling pathway in a type 2 diabetic rat model (Qi et al 2015). Naringin protects neural cells on 3-nitropropionic acid-induced mitochondrial dysfunction through modulation of Nrf2 signaling pathway (Kulasekaran and Ganapasam 2015). Naringin induces autophagy-mediated growth inhibition by downregulating the PI3K/Akt/mTOR cascade via activation of MAPK pathways in AGS cancer cells (Raha et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The PC12 cell line is a widely used experimental model for neuroprotection and neurodegeneration analysis, particularly in the contexts of excitotoxicity [30,31], whereas 3-nitropropionic acid is usually applied as a neurotoxic agent trigger for mitochondrial dysfunction [13]. We used both in our in vitro study for the examination of the potential protective action of the ethanolic extract of A. asphodeloides against neurotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3-NP is a specific inhibitor of the mitochondrial complex II electron transport chain, so it consequently leads to an excessive ROS production, mitochondrial DNA damage, and loss of the physiological function of mitochondria. Hence, 3-NP induces cell death, via necrosis or apoptosis, especially these in the nervous system [13,14]. Some in vivo research has indicated that 3-NP acts on cortical activity, but its overall effect is complex, involving elements of depression and excitation, which is important in neurodegenerative pathogenesis.…”
Section: Introductionmentioning
confidence: 99%